2014
DOI: 10.3171/2013.12.spine13653
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous atraumatic vertebral artery occlusion due to physiological cervical extension

Abstract: Vertebral artery (VA) occlusion is a serious and potentially life-threatening occurrence. Bow hunter's syndrome, a mechanical occlusion of the VA due to physiological head rotation, has been well described in the medical literature. However, mechanical VA compression due to routine flexion or extension of the neck has not been previously reported. The authors present the unique case of a woman without any history of trauma who had multiple posterior fossa strokes and was found to have dynamic occlusion of her … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“… 2 Bow Hunter’s syndrome is a mechanical occlusion of the VA due to physiological head rotation. 3 Vertebral artery injury (VAI), may result from penetrating injuries, chiropractic manipulation, prolonged abnormal positioning of the neck, birth trauma or from closed head or neck trauma. Nevertheless, damage to the artery as a result of closed injury is considered to be rare.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Bow Hunter’s syndrome is a mechanical occlusion of the VA due to physiological head rotation. 3 Vertebral artery injury (VAI), may result from penetrating injuries, chiropractic manipulation, prolonged abnormal positioning of the neck, birth trauma or from closed head or neck trauma. Nevertheless, damage to the artery as a result of closed injury is considered to be rare.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that this is why the McKenzie cervical approach has been shown to be successful in managing mechanically induced pain and related symptoms. 28,29 The current study suggests that the McKenzie cervical approach could address conditions related to VA insufficiency. However, this is only a hypothesis because the current study only measured healthy participants.…”
Section: Discussionmentioning
confidence: 78%
“…For example, neck rotation, extension, and loss of cervical lordosis can cause luminal narrowing and reduce the VA blood flow, which might lead to a mechanical occlusion to the VA. It has been suggested that 29,30 neck rotation can compress to the VA through the dynamic stretching to the facet that can stretch the VA, where axial rotation of the cervical spine places the VA under high strain force. 31 In contrast, another study found minimal effects from head and neck positions on the VA blood flow.…”
Section: Introductionmentioning
confidence: 99%
“…There were 22 patients with BHS due to embolic mechanisms, including the present case, as shown in Table 1. 3,[5][6][7][8][9][10][11][12][13][14][15][16][17][18] The overall mean age of the patients was 31 ± 22 years (Table 2). BHS due to an embolic mechanism was observed in 20 men and 2 women.…”
Section: Results Of the Literature Reviewmentioning
confidence: 99%